Physiological Response of the Body to Heat Exposure in Workers - Desta Bulan Cahyarani; Winda Trijayanthi Utama; Maya Ganda Ratna; Sutarto Sutarto (Lembaga Pengembangan Kinerja Dosen, 2025)
Heat is a prevalent and serious physical health risk for employees in a range of indoor and outdoor work settings. Heat stress at work alters physiological processes and has a variety of detrimental consequences on people's health and wellbeing. This study aimed to explore the physiological responses and impacts of heat exposure in outdoor workers. This study employed a literature review approach using Google Scholar, Wiley, and Pubmed databases. The results will be described through descriptive narratives and tables. Workers exposed to heat experience increased physiological reactions, including increased body temperature, heart rate, and blood pressure, especially those engaging in intense physical activity outdoors. Heat-related symptoms such as fatigue, excessive sweating, headaches, and muscle cramps can also occur in heat-exposed workers. These increased and altered physiological responses emphasize the importance of implementing preventative measures, such as managing work hours, maintaining hydration, and maintaining good health, to avoid heat-related illnesses and maintain workplace productivity.